Dynamic performance of collar plate reinforced tubular T-joint with precompression chord. (15th June 2017) - Qu, Hui; Li, Anling; Huo, Jingsi; Liu, Yanzhi
Highlights: Collar plate reinforcement can significantly improve and change the impact behaviour and failure mode of tubular T-joints. Fe model can reasonably capture the failure mechanism of T-joints. Equivalent area method can be used to estimate the local indentation and global bending deformation of tubular T-joint. Abstract: This paper examines the dynamic behaviour of collar plate reinforced tubular T-joints with precompression chord by means of experimental and numerical studies. An experimental programme involved one test on unstiffened tubular T-joint and three on stiffened configurations is carried out through a high-performance drop hammer machine. A series of disc springs is installed to apply axial compression to the chord. The dynamic response of four tubular T-joints are described and discussed with emphasis on the effect of the stiffener, especially for dimensional parameters of collar plate. Based on the experimental results, the key behavioural patterns including the development of impact force, deformation and strain, as well as deformation modes are identified. The impact mechanism is also investigated. The finite element (FE) models of the tubular T-joints subjected to impact loadings are then developed by commercial software of ABAQUS, where nonlinear material behaviour and pre-compressive loads are all considered. The numerical findings exhibit close agreement with experimental results in terms of failure pattern as well as the development of impact force and the corresponding displacements. Finally, the dynamic performance of unreinforced and collar plate reinforced tubular T-joints is revealed based on the numerical simulation. Particularly, the joint deformation and impact resistance are examined by the equivalent area method and the formula in NORSOK Standard, respectively. In general, the presence of collar plate stiffeners significantly improves the impact resistance of tubular T-joints.